(untitled) (Revista Latino-Americana de Enfermagem, 2011)
Early isolation of patients possibly colonized by multi-resistant microorganisms can minimize their spread, reducing cases of hospital infection and the related costs. This study aimed to identify the sensitivity and specificity of the criteria for isolation of patients admitted to a specialized cancer hospital. Cross-sectional study with a population of 61 patients coming from other hospitals who were admitted to the hospital between March 1st and August 31th, 2009. At the moment of admission, a data collection instrument was filled out and nasal and anal swabs were collected for microbiological culture. Of the 56 patients who met the isolation criteria, 30 (49.2%) presented positive cultures for multi-resistant microorganisms and methicillin-resistant Staphylococcus aureus was the most frequently identified microorganism. Most patients colonized by multi-resistant microorganisms were isolated at the moment of admission. The sensitivity of the isolation criteria was 90% and the specificity was 6.5%.